Inclusion Properties of Certain Subclasses of Analytic Functions Involving Mittag-Leffler Function - F. Z. El-Emam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of the present paper is to introduce certain new subclasses of analytic univalent functions defined by a linear operator involving Mittag-Leffler function and study their inclusion relationships. Some applications involving integral operators are also considered.